A alfabetização científica na educação básica e pública: fatores necessários para o seu desenvolvimento no ensino de Ciências - Borges, Katia Cilene Alves (2024)
Science exerts a great influence on our daily life, being the main engine of technical and technological development, to the point that it is difficult to imagine what the current world would be like without its contribution and the importance that it exerts in society is undeniable. Because of these aspects, it is essential that basic education students experience activities that are characteristic of scientific culture Through this research, with a qualitative approach we intend to investigate what are the strategies and actions related to scientific literacy present in public schools that present selected and awarded works at the Science Fairs of Mato Grosso do Sul - FETEC and FECITEC. The locus of collection will include schools from the municipal and state network of Campo Grande, MS, selected after analyzing the annals of the fairs, based on the criterion of the largest number of presentations and awards for studies and research. Note that full-time schools or those participating in the “Escola da Autoria” program will not be included. The investigation will cover three distinct phases: a) Bibliographic and documentary phase; b) Phase of field collection; c) Phase of treatment, analysis and systematization of results. In the bibliographic phase, a Systematic Review will be carried out aiming to analyze how Scientific Literacy has been developed in Science Teaching in Basic Education in Brazil. In the field collection, interviews will be carried out with the management, technical team and teachers of the selected schools, through the observance of the ethical aspects of the research. All speeches will be transcribed and confronted with the theoretical bases of the study. Data interpretation will be done using the content analysis method. It is expected with this study to identify which are the factors present in public schools of basic education, which allow the effective development of pedagogical practices for Scientific Literacy. They are: Practically, all teaching units investigated have research laboratories and all teachers develop theoreticalpractical activities that stimulate scientific literacy using the laboratories or not. Given the nature of our investigation, we also confirmed that the participants in this research consider the importance of having a consistent theoretical basis and having good coexistence between all segments of the school community. The difficulties in developing research and other actions guiding Scientific Literacy were also highlighted among all participants. The main ones are the lack of time and resources, external demands and the lack of employees to assist in research. There was also a consensus on the importance of continued training for teachers, however, we noticed that there is awareness of the importance of these trainings in all segments, however, the demands and the recognition of prioritizing are not yet proposed in schools by these professionals. Regarding the importance of Scientific Literacy, both teachers and technical staff consider traditional science teaching to be ineffective. Given this context, it is possible to preliminarily consider that the achievement of Scientific Literacy requires the delineation of a series of factors, such as: training and studies of the proposed theme, improvement in the working conditions of education professionals, maintenance and increase in resources financial, structural and human in public education, democratic/participatory management, good coexistence between segments.